Arthur and Ron Felix and Bernie Rouzes play songs and talk about music - Thomas, Gerald (1971)
Arthur et Ron Felix et leur ami Bernie Rouzes jouent de la musique et discutent de la provenance des chansons. Ils jouent, entre autres, « Tootsie Wootsie » et « la gigue à Émile ». -- Arthur and Ron Felix and their friend Bernie Rouzes play some music and discuss the provenance of the songs they know. They play, among other songs, "Tootsie Wootsie" and "Émile's Jig".